Discovery Learning dan Metode Diskusi Kelompok untuk Meningkatkan Hasil Belajar Ekonomi Peserta Didik pada Pokok Bahasan Perpajakan di Kelas XI IPS 1 SMAN 1 Payakumbuh Semester Genap Tahun Pelajaran 2017/2018 - Suryani, Fefy (Jurusan PIPS FKIP UMMY Solok, 2019)
This study aims to look at and analyze the improvement of the students’ learning outcomes in learning Economics subject of taxation in economic development using the scientific approach to the discovery learning model and group discussion methods in class XI IPS 2 on the second semester of the 2017/2018 academic year of SMAN 1 Payakumbuh, West Sumatra. This research was carried out by applying the classroom action research method consisting of two cycles, where each cycle consisted of: planning, action, observation, and reflection. It was conducted from February to April 2018. Data is processed in each cycle then analyzed using percentages. The results obtained from this study are the application of a scientific approach to the discovery learning model and the method of group discussion can improve student learning outcomes. This is evident from the average cognitive learning outcomes in the first cycle of 80.20%, up to 84.23% in the second cycle. The conclusion obtained from this study is the application of a scientific approach to the model of discovery learning can improve the learning outcomes of economic learners.